2021
DOI: 10.1371/journal.pone.0247634
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and predictors of poor glycemic control among patients with diabetes attending public hospitals of Western Ethiopia

Abstract: Background Diabetes is one of the most prevalent non-communicable diseases globally, which rapidly is increasing in developing countries. Ethiopia is also facing growing morbidity and mortality related to diabetes complications. Thus, dealing with glycemic control is essential for controlling the development of devastating acute and chronic complications related to diabetes. Therefore, this study aims to assess the magnitude and predictors of poor glycemic control among diabetic patients in western Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
(35 reference statements)
7
29
1
Order By: Relevance
“…In this study, a high-level prevalence of poor glycemic control was presented among study participants who were on insulin treatment (40%) and Oral anti–diabetic drugs (42.1%). The results were lined with other studies [ 20 , 40 ]. Starting insulin therapy for T2DM patients often showed blood glucose level is not well controlled [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a high-level prevalence of poor glycemic control was presented among study participants who were on insulin treatment (40%) and Oral anti–diabetic drugs (42.1%). The results were lined with other studies [ 20 , 40 ]. Starting insulin therapy for T2DM patients often showed blood glucose level is not well controlled [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Most study participants were obese or overweight, which is expected with their low level of physical activity; those with higher BMI (obesity) were more likely to have poor glycemic control compared to those with normal BMI, supporting previous findings. 13 , 52 Many studies found BMI has associated with glycemic control but is not an independent predictor. 15 , 16 , 18 , 24 Conversely, some studies reported that patients with normal BMI were more likely to have poor glycemic control than overweight and obese patients, which was explained by the disease process of diabetes where poor glycemic control is associated with weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Unfortunately, poor control of diabetes is widely prevalent worldwide. [8][9][10][11][12][13][14][15][16][17][18] Different rates of poorly controlled T2DM were revealed in various countries, such as 49.4-74.9% in Saudi Arabia, 19,20 54% in Oman, 21 69.6% in Libya, 11 67.5% in Turkey, 4 64.1-70.9% in Ethiopia, 13,22 69.7% in Tanzania, 23 61.3% in Zambia, 24 72.6-83% in Pakistan, 8,9 40% in Malaysia, 25 89% in China, 10 and 66% in the United States. 26 In Jordan, poorly controlled T2DM ranged from 56.5% to 83.8%.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated using a single population proportion formula with 95% confidence interval, 64.1% [ 13 ] proportion and a margin of error 5% i.e. N = = 354 and by adding 10% for nonresponse the final sample size was 390.…”
Section: Methodsmentioning
confidence: 99%